TATHWÎR AL-NAMÛDZAJ AL-TA’LÎMÎ LI MAHÂRAH AL-KALÂM FI DHAU AL-FURÛQ AL-FARDHIYAH FÎ AL-JÂMI’AH AL-ISLÂMIYAH AL-HUKÛMIYAH - Suharmon Suharmon; Mohammad Ainin; Torkis Lubis (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2019)
This research aims to develop Individual Differences-Based Speaking Skills Learning Model in Arabic Language Education Program of Institute for Islamic studies Batusangkar. The Research questions to answer are how to design, how is praticality and than effectiveness of the model. The Research and Development Method appload Dick and Carry Development Model. The results of this research are as follows: 1) The design of the learning model is based on three student groups; 2) In terms of practicality, 87% of the students are able and to solvie problems in the process of learning Arabic, 67% of the students are confident to be able to speak Arabic; 3) In terms of effectiveness, the use of this learning model has an effect on improving  the  student’s learning outcomes, This is indicated by  the “ t “ test result 2,036 ˂ 7,110 ˃ 2,036. The research concludes that the model is feasible, practical, and effective in improving, the student’s speaking skills.